Efficacy and Safety of Endoscopic Papillary Balloon Dilation Using Cap-Fitted Forward-Viewing Endoscope in Patients Who Underwent Billroth II Gastrectomy - Jang, Jong Soon; Lee, Seungho; Lee, Hee Seung; Yeon, Myeong Ho; Han, Joung-Ho; Yoon, Soon Man; Chae, Hee Bok; Youn, Sei Jin; Park, Seon Mee (Clinical endoscopy, 2015)
Endoscopic exploration of the common bile duct (CBD) is difficult and dangerous in patients with Billroth II gastrectomy (B-II). Endoscopic papillary balloon dilation (EPBD) via a cap-fitted forward-viewing endoscope has been reported to be an effective and safe procedure. We analyzed the technical success and complications of EPBD in patients who underwent B-II. Thirty-six consecutive patients with B-II were enrolled from among 2,378 patients who had undergone endoscopic retrograde cholangiopancreatography in a single institute in the last 4 years. The EPBD procedure was carried out using a cap-fitted forward-viewing endoscope with 8-mm balloon catheters for 60 seconds. We analyzed the rates of CBD exploration, technical success, and complications. Afferent loop intubation was performed in all patients and selective cannulation of the bile duct was performed in 32 patients (88.9%). Complications such as transient hypoxia were observed in two patients (5.6%) and perforation, in three patients (9.7%). The perforation sites were ductal injury in two patients and one patient showed retroperitoneal air alone without symptoms. Three patients manifested different clinical courses of severe acute pancreatitis and peritonitis, transient abdominal pain, and retroperitoneal air alone. The condition of one patient improved with surgery and that of the other two patients, with conservative management. Patients with perforation during EPBD in B-II showed different clinical courses. Tailored treatment strategies are necessary for improving the clinical outcomes.